2016
DOI: 10.1038/srep32410
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial role in adaptive response to stress conditions in preeclampsia

Abstract: Preeclampsia (PE) is a pregnancy-specific syndrome, characterized in general by hypertension with proteinuria or other systemic disturbances. PE is the major cause of maternal and fetal morbidity and mortality worldwide. However, the etiology of PE still remains unclear. Our study involved 38 patients: 14 with uncomplicated pregnancy; 13 with early-onset PE (eoPE); and 11 with late-onset PE (loPE). We characterized the immunophenotype of cells isolated from the placenta and all biopsy samples were stained posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
70
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 50 publications
(56 reference statements)
8
70
3
Order By: Relevance
“…This work observed that the activity of CS in the liver increased with DEX treatment. The result is accorded with the report that OS could increase the activity of citrate synthase in mitochondria (Sheeran & Pepe, ; Vishnyakova et al., ). Also, citrate inhibits phosphofructokinase‐1 (the rate‐limiting enzyme of glycolysis).…”
Section: Discussionsupporting
confidence: 91%
“…This work observed that the activity of CS in the liver increased with DEX treatment. The result is accorded with the report that OS could increase the activity of citrate synthase in mitochondria (Sheeran & Pepe, ; Vishnyakova et al., ). Also, citrate inhibits phosphofructokinase‐1 (the rate‐limiting enzyme of glycolysis).…”
Section: Discussionsupporting
confidence: 91%
“…Other genes were regulated by R. rosea HRE but their modulation depended more strongly on the brain structure considered. In the amygdala, the R. rosea HRE and acute mild stress interaction damped the expression of ND2, a mitochondrial membrane respiratory chain gene, suggesting an essential role of mitochondrial activity as an adaptive response to stress, as previously proposed (Vishnyakova et al, ). In the PFC, BHLHB2, a gene implicated in neurotrophic factor activity and neuronal excitability, was upregulated by R. rosea HRE, suggesting improved communication between neurons.…”
Section: Discussionsupporting
confidence: 75%
“…Recently, Professor Gennady Sukhikh’s Research Institute in Moscow has reported the following findings, indicating that mitochondrial functional changes in the placenta occur in both early- and late-onset preeclampsia when compared to normal pregnancy(208):…”
Section: Mechanisms By Which Metformin May Prevent Preeclampsiamentioning
confidence: 99%
“…This gene is involved in mitochondrial fusion and in the cristae structure of the inner mitochondrial membrane, a fine-tuned process crucial for mitochondrial quality control; 2) a five-fold decrease in the mitochondrial transcription factor (TFAM)-A; 3) a 1.5-fold increase of the relative placental mitochondrial DNA copy number; and 4) increased mitochondrial respiration in the presence of Complex I substrates(208). …”
Section: Mechanisms By Which Metformin May Prevent Preeclampsiamentioning
confidence: 99%
See 1 more Smart Citation